Kajian Semiotika Tuturan Mantra Tradisi Pertunjukkan Jaranan di Desa Perangat Baru Kecamatan Marangkayu Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Indrahastuti, Tri; Nurcahya, Rizki Aditya; Balfas, Anwar (Adjektiva: Educational Languages and Literature Studies, 2018)
Literature is an expression of the human person in the form of experiences, thoughts, feelings, ideas, passions, beliefs in a form of concrete images that evoke charm with language tools. Jaranan performance is a ritual art activity carried out by the community as entertainment for the people of the village of Warat Baru and also to resist reinforcements. Semiotics is a science that studies a sign and the meaning in a sign, which is divided into three types, namely icons, indexes and symbols. The purpose of this study is to describe the shape of icons, indices and symbols in the speech of the Jaranan performance mantra in Prangat Baru village, Marangkayu district, Kutai Kartanegara regency. The data collection method used in this research is qualitative research, namely observation, structured interviews, recording, and collection tools in the form of interview instruments, recordings, photos, videos, and translation. The results of the research from the data of mantra speech using semiotic analysis obtained 3 utterances in the form of the 'Prince' icon, 'Sesaji', 'incense lan sela'. Obtained 4 indexes 'Sun Puji Maring Pangeran Mugi Sometimes Mitro Sami', 'Suro Diro Joyo Diningrat Melts Dening Pangastuti', 'Enjoy the offering of supados, enjoy smoothness and protection', 'kula sukani, let Kangge eat the ringgit wayangipun kula'. Get 3 symbols 'Yellow Janur', 'Semeblak koyo Geni', 'Jabang Bayine'. Obtained 4 indexes 'Sun Puji Maring Pangeran Mugi Sometimes Mitro Sami', 'Suro Diro Joyo Diningrat Melts Dening Pangastuti', 'Enjoy the offering of supados, enjoy smoothness and protection', 'kula sukani, let Kangge eat the ringgit wayangipun kula'. Get 3 symbols 'Yellow Janur', 'Semeblak koyo Geni', 'Jabang Bayine'. Obtained 4 indexes 'Sun Puji Maring Pangeran Mugi Sometimes Mitro Sami', 'Suro Diro Joyo Diningrat Melts Dening Pangastuti', 'Enjoy the offering of supados, enjoy smoothness and protection', 'kula sukani, let Kangge eat the ringgit wayangipun kula'. Get 3 symbols 'Yellow Janur', 'Semeblak koyo Geni', 'Jabang Bayine'.